Beyond Tolerance: Dinamika Komunikasi Antarbudaya Dalam Penguatan Moderasi Beragama Pada Keluarga Beda Agama Di Karang Baru Utara, Mataram - Audiva Amaryllys Sukardi (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze in depth the dynamics of intercultural communication in strengthening religious moderation within interfaith families in Karang Baru Utara, Mataram City. It employs a qualitative approach with a case study design and was conducted in Karang Baru Utara, Selaparang District, Mataram City, West Nusa Tenggara. Data were collected through observation, in-depth interviews, and documentation, involving interfaith families as primary informants. Data analysis followed the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. Data validity was ensured through source, method, and time triangulation, as well as member checking, to maintain credibility and trustworthiness. The findings reveal that communication within interfaith families unfolds as a dialectical process involving identity negotiation, the management of differences, and the continuous construction of meaning. Social harmony is not achieved automatically but is constructed through daily communication practices characterized by reflexivity, empathy, and adaptability. Local cultural values, such as *gotong royong* (mutual cooperation), further strengthen intercultural communication within the family. The study suggests that religious moderation should be understood as an active communication practice rather than merely a normative stance, positioning the family as a strategic space for developing inclusive and dialogic communication models within a pluralistic society.